Repeated influenza vaccination induces similar immune protection as first‐time vaccination but with differing immune responses. Issue 1 (21st October 2022) - Ye, Beiwei; Shu, Liumei; Pang, Yuanyuan; Guo, Yaxin; Guo, Yuanyuan; Zong, Kexin; Chen, Cong; Zheng, Xianzhi; Zhang, Jie; Liu, Maoshun; Yuan, Xiaoju; Zhao, Yingze; et al.
Abstract: Background: Recent seasonal epidemics of influenza have been caused by human influenza A viruses of the H1N1 and H3N2 subtypes and influenza B viruses. Annual vaccination is recommended to prevent infection; however, how annual influenza vaccination influences vaccine effectiveness is largely unknown. Methods: To investigate the impact of repeated vaccination on immune and protective effect, we performed a prospective seroepidemiologic study. Participants with or without prior vaccination (2018–2019) were enrolled during the 2019–2020 influenza season. Inactivated quadrivalent influenza vaccine (IIV4) was administered through the intramuscular route, and venous blood samples were collected regularly to test hemagglutination inhibition (HAI) titers. Results: The geometric mean titers and proportion with titers ≥40 against the influenza vaccine components peaked at 30 days post‐vaccination. At Day 30, the geometric mean titer and proportion with titers ≥40 in participants who had been previously vaccinated were higher for H3N2 but similar for both B lineages (Victoria and Yamagata) as compared with participants vaccinated for the first time. As for H1N1, the geometric mean titer was lower in repeated vaccinated participants, but the proportion with titers ≥40 was consistent in both groups. Conclusions: Repeated vaccination provides similar or enhanced protection as compared with single vaccination in first‐time vaccinees.